2001
DOI: 10.1038/sj.jhh.1001229
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure determinants of left ventricular wall thickness and mass index in hypertension: comparing office, ambulatory and exercise blood pressures

Abstract: Left ventricular (LV) mass relates positively and continuously to cardiac mortality and thus its regression is a rational therapeutic aim. Whilst the office blood pressure (BP) relates poorly to LV mass, it was unclear whether the 24-h ambulatory BP or the exercise systolic BP (ExSBP) was the stronger correlate of LV structural indices. We studied 49 hypertensive patients with a mean age of 45 (s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Excessive blood pressure elevation during physical exertion has been shown to contribute to impaired exercise tolerance in hypertensive patients even in the absence of coronary artery disease or left ventricular dysfunction (9,29,33,50). Furthermore, numerous epidemiological studies have demonstrated that exercise blood pressure predicts the pathogenesis of left ventricular hypertrophy, stroke, myocardial infarction, and death (12,23,27,28,65) independent of resting ABP. Accordingly, current safety guidelines prohibit exercise in hypertensive patients if exertional ABP reaches or exceeds 220/105 (15,51).…”
Section: Perspectives and Clinical Significancementioning
confidence: 99%
“…Excessive blood pressure elevation during physical exertion has been shown to contribute to impaired exercise tolerance in hypertensive patients even in the absence of coronary artery disease or left ventricular dysfunction (9,29,33,50). Furthermore, numerous epidemiological studies have demonstrated that exercise blood pressure predicts the pathogenesis of left ventricular hypertrophy, stroke, myocardial infarction, and death (12,23,27,28,65) independent of resting ABP. Accordingly, current safety guidelines prohibit exercise in hypertensive patients if exertional ABP reaches or exceeds 220/105 (15,51).…”
Section: Perspectives and Clinical Significancementioning
confidence: 99%
“…In contrast to peak exercise BP, which is highly effort-dependent and affected by fitness level, exercise BP measured during sub-maximal exercise represents a physiological response to low-to-moderate physical activity that is closely correlated with ambulatory BP, 11 mean daily BP and end-organ damage. 12 Understanding the clinical and vascular correlates of exercise BP response to moderate exercise may provide mechanistic insights into the development of hypertension, left ventricular hypertrophy (LVH) and CVD.…”
mentioning
confidence: 99%
“…Adding to this list, our study demonstrated that dietary Pi excess detrimentally affects the sympathetic regulation of BP during exercise by potentiating the function of both the muscle mechanoreflex and metaboreflex, the two major components of the EPR and, in doing so, may contribute to the pathogenesis of Pi-induced hypertension. Just as important, numerous epidemiological studies have demonstrated that exercise BP predicts subsequent development of stroke, myocardial infarction, and death (20,23,24,47), independent of resting BP.…”
Section: Discussionmentioning
confidence: 99%